2000
DOI: 10.1136/pmj.76.902.774
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome

Abstract: Guillain-Barré syndrome is an autoimmune disorder encompassing a heterogeneous group of pathological and clinical entities. Antecedent infections are thought to trigger an immune response, which subsequently cross reacts with nerves leading to demyelination or axonal degeneration. Both intravenous immunoglobulin treatment and plasma exchange have been found to be equally beneficial. Several factors are useful in predicting the outcome of these patients. (Postgrad Med J 2000;76:774-782)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 111 publications
2
22
0
2
Order By: Relevance
“…Ho TW, et al in Western China study 11 show AIDP -19%, AMAN 65%, AMASAN 10-15%. Udaya Senevaratne, Srilanka Study (2000) 12 shows, 76% AIDP, 24% AMAN and 10% comprises other subtype of GBS which was comparable to our study. Rong KL, et al (1997) 13 Taiwan study showed AIDP (49%), AMAN (4%), MFS (18%) and others 29%.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Ho TW, et al in Western China study 11 show AIDP -19%, AMAN 65%, AMASAN 10-15%. Udaya Senevaratne, Srilanka Study (2000) 12 shows, 76% AIDP, 24% AMAN and 10% comprises other subtype of GBS which was comparable to our study. Rong KL, et al (1997) 13 Taiwan study showed AIDP (49%), AMAN (4%), MFS (18%) and others 29%.…”
Section: Discussionsupporting
confidence: 81%
“…In Emilia Romagna study in Italy (1999) 14 65% cases had associated infection (59% fever, 18.2% diarrhea); Cheng Q, et al Sweden study (2000) 18 shows 60% respiratory tract illness, 28% diarrhea, 45% RTI. Paul H, et al (2001) 19 study show 71% associated illness, Udaya Seneviratne, Srilanka study (2000) 12 show 60% associated illness (20% Diarrhea, 40% Respiratory tract infection), Nicholas DL, et al 20 study shows 71% associated illness, Taiwan study (1997) show 67% associated illness (54% respiratory infection). Jacob BC,et al Netherlands study (1998) 21 show 32% diarrhea and 19% respiratory tract illness.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to distinguish RGBS from two clinical entities; (1) GBS with treatment related fluctuations (GBS-TRF), (2) Chronic inflammatory demyelinating polyneuropathy (CIDP). Since our patient had a long asymptomatic period, GBS-TRF is less likely but CIDP comes as a differential diagnosis.…”
Section: Investigationsmentioning
confidence: 99%
“…This results in marked inflammation of the peripheral nerves, resulting in demyelination and defective impulse propagation. It is a heterogeneous group of disorders which involves motor, sensory and autonomic nervous systems to varying degrees depending on the sub type; [1] Acute inflammatory demyelinating polyneuropathy, [2] Acute motor axonal neuropathy, [3] Acute motor sensory axonal neuropathy, [4] Miller Fisher syndrome, [5] Acute pan-autonomic neuropathy and [6] Pure sensory GBS.…”
Section: Investigationsmentioning
confidence: 99%
“…[1][2][3][4] However, severe neurological complications involving the peripheral nervous system (PNS) are relatively rare, occurring in less than 3% of transplanted patients and presents with acute or chronic inflammatory demyelinating polyneuropathy. 2,[4][5][6][7][8] An alternative approach for allogeneic SCT, aimed at attenuating treatment-related toxicity by reducing the conditioning chemotherapy dose and increasing the cure rate by inducing a graft-versus-tumour effect, has recently been introduced in patients with haematological malignancies. [9][10][11][12] We describe the incidence, characteristics and outcome of neurological complication following alemtuzumab-based reduced-intensity SCT (RISCT), emphasizing the relatively high incidence of PNS involvement observed in these patients.…”
mentioning
confidence: 99%